Vulnerable hot spots to water and agricultural risk in Sri Lanka - Amarasinghe, Upali A.; Amarnath, Giriraj; Alahacoon, Niranga (2020)
The Nationally Determined Contributions (NDCs) addressing the challenges of climate change in Sri Lanka (CCS, 2016a) have four components: adaptation, mitigation, assessment of losses and damages, and means of implementation. For adaptation, the National Adaptation Plan (NAP) identified food security (agriculture, livestock, and fisheries) and water resources as key sectors requiring immediate attention. The other sectors of interest in the NAP are coastal and marine; health; human settlements and infrastructure; ecosystems and biodiversity; tourism and recreation; export agriculture; and industry, energy, and transportation (CCS, 2016b). However, knowledge and information gaps on climate and other exogenous risks are significant barriers to the implementation of adaptation plans.